When Did Growth Begin? New Estimates of Productivity Growth in England from 1250 to 1870 - Bouscasse, Paul; Nakamura, Emi; Steinsson, Jón (Quarterly Journal of Economics, 2025)
Abstract We estimate productivity growth in England from 1250 to 1870. Real wages over this period were heavily influenced by plague-induced swings in the population. Our estimates account for these Malthusian dynamics. We find that productivity growth was zero before 1600. Productivity growth began in 1600—almost a century before the Glorious Revolution. Thus, the onset of productivity growth preceded the bourgeois institutional reforms of seventeenth-century England. We estimate productivity growth of 2% per decade between 1600 and 1800, increasing to 5% per decade between 1810 and 1860. Much of the increase in output growth during the Industrial Revolution is explained by structural change—the falling importance of land in production—rather than faster productivity growth. Stagnant real wages in the eighteenth and early nineteenth centuries—Engels’ Pause—is explained by rapid population growth putting downward pressure on real wages. Yet feedback from population growth to real wages is sufficiently weak to permit sustained deviations from the “iron law of wages” prior to the Industrial Revolution.